Homoerotic space : the poetics of loss in Renaissance literature - Guy-Bray, Stephen (Book collections on Project MUSE., 2002)
Stephen Guy-Bray argues that early modern authors used renditions of Theocritan and Virgilian pastoral, as well as epic poetry, for the exploration and the allusive presentation of homoerotic and homosocial themes.